O uso da rede social facebook como ferramenta para ensino da ortografia em séries finais do ensino fundamental: o caso da hipossegmentação - Carvalho, André Luiz Brito de (2018)
The fact that spelling has always been the subject of doubts and concerns for students of the most different age groups, often due to the teaching methods used by the teachers, which did not lead the student to reflect on why a certain word was written in that way or the reason that he committed certain types of errors motivated the research, which set out to investigate the main orthographic errors committed by students in the final grades of Elementary School, finding in the hypothesis phenomenon a recurrence that caught the researcher's attention. from there he looked for alternatives for a more productive teaching, finding in the social network Facebook an important tool for working with spelling. A qualitative research was developed, seeking to deepen the alternatives to traditional teaching and to make learning spelling efficient. According to Lemle (2007), the teacher must know a little about the morphological structure and history of Portuguese to explain to the students about orthographic conventions, but what should be done is to look for practical methodologies that can facilitate the understanding of the student about their mistakes. Based on the studies of Morais (2007a, 2007b, 2007c, 2008), Chacon (2004), Capristano (2003), Tenani (2009a, 2010, 2011a, 2011b) and Nespor and Vogel (1986), a pre-test occurred in April and May 2017 and a post-test in December of the same year. The result showed that, despite the difficulties already expected, it is possible to use social networks as an object of learning, since 56% of the students scored 60% of the words, which proves that there was an advance in the knowledge of the rule.